1992
DOI: 10.1161/01.hyp.20.3.319
|View full text |Cite
|
Sign up to set email alerts
|

Hematocrit, blood pressure, and hypertension. The Gubbio Population Study.

Abstract: Baseline data from the Gubbio Population Study in north central Italy were used to investigate the relation of hematocrit to blood pressure and hypertension among 2,809 men and women aged 25-74 years. Independent of gender, age, and other confounders, the hypertensive group had a higher hematocrit than the nonhypertensive group (p<0.001). In comparison with the untreated hypertensive group, the hypertensive group being treated with diuretics or with other drugs only had similar mean hematocrit levels despite s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
53
4
7

Year Published

1995
1995
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(80 citation statements)
references
References 31 publications
12
53
4
7
Order By: Relevance
“…These findings are similar to the earlier findings by Giacomo et al [7], Massimo et al [8], Dan et al [9] and Al-Muhana et al [10].…”
Section: Hemoglobin and Erythrocyte Countsupporting
confidence: 93%
See 2 more Smart Citations
“…These findings are similar to the earlier findings by Giacomo et al [7], Massimo et al [8], Dan et al [9] and Al-Muhana et al [10].…”
Section: Hemoglobin and Erythrocyte Countsupporting
confidence: 93%
“…Alternative possibilities are that hematocrit contributes to the regulation of blood pressure or that some other factors are responsible for parallel changes of hematocrit and blood pressure. The role of other (possibly dietary) factors not considered in the present study cannot be excluded [8].…”
Section: Hemoglobin and Erythrocyte Countmentioning
confidence: 92%
See 1 more Smart Citation
“…Previous investigations into the effects of hematocrit on blood pressure have variously found that it is either related [1][2][3][4][5] or unrelated 6,7) to hypertension. These inconclusive results may have been resulted in part from ethnic or lifestyle differences in the study populations but also may have been strongly influenced by different methods used to investigate the association between hematocrit and hypertension.…”
mentioning
confidence: 99%
“…However, population-based studies have consistently demonstrated that, on average, [Hb] is raised in patients with essential hypertension (13). Thus, it appears plausible that Hb-dependent mechanisms influencing NO bioavailability contribute to endothelial dysfunction in hypertension.…”
Section: Introductionmentioning
confidence: 99%